Sustainable Development in South Asia: A Strategic Inquiry into Pakistan-Neighbors Trade Dynamics - Fatima, Manal; Junaid, Zubair Bin (Unisia, 2024)
The study aims to comprehensively analyze Sustainable Development in South Asia while look into the trade dynamics between Pakistan and its neighboring countries. Exploring different regional trade arrangements can help with understanding the influence of different markets and unions on trade in South Asia. Regional trading blocks are heavily impacted by static and dynamic economic effects. The South Asian Association for Regional Cooperation (SAARC) and initiatives like the South Asian Free Trade Area (SAFTA) are examined for their potential to enhance regional trade. The paper also delves into the impact of non-economic factors with regard to South Asia. Pakistan and India are two very important countries in South Asia, however both countries are yet to work towards practical solutions of the existing stand-offs between them. The results show that this can be done by the entrepreneurs of the two countries with paper support from their governments, institutions and international trade bodies, so that the two countries can lead a brighter future without any conflicts.